Social deterministic factors to participation in the National Health Insurance Scheme in the context of rural Ghanaian setting - Stephen Manortey; Steve Alder; Benjamin Crookston; Ty Dickerson; James VanDerslice; Scott Benson (AOSIS, 2014)
The primary purpose of this study is to identify predictors of complete household enrollment into the National Health Insurance Scheme (NHIS) among inhabitants of the Barekese sub-district in the Ashanti Region of Ghana. Heads of households in 20 communities from the Barekuma Collaborative Community Project site were interviewed to gather data on demographic, socioeconomic status (SES) indicators and complete household subscription in the NHIS. Logistic regression model was used to predict enrollment in the NHIS. Of the 3228 heads of households interviewed, 60 percent reported having all members of their respective households enrolled in the NHIS. Residents in the classified Middle and High SES brackets had 1.47 (95% CI: 1.21-1.77) and 1.66 (95% CI: 1.27- 2.16) times higher odds, respectively, of complete household enrollment compared to their counterparts in the Low SES category. The odds of enrolling in the program tend to increase progressively with the highest level of education attained by the head of the family unit. Eight years after the introduction of the national health insurance policy in Ghana, the reported subscription rate for complete households was about 60 percent in the 20 rural communities that participated in the study. This finding calls for the need to step up further national strategies that will help increase enrollment coverage, especially among the poor and less educated in the rural communities.